The invention, gaming, and persistence of the hensachi ('standardised rank score') in Japanese education - Goodman, R; Oka, C (Taylor and Francis, 2018)
This paper explores the development of the hensachi system in Japanese education from the 1960s when it first appeared as a de facto measure for scholastic achievement. Unlike absolute scoring systems (such as A-level grades) hensachi gave an indication of the probability of getting a place on a particular course at a particular school or university rather than telling applicants where the bar was set in order to have a chance of being offered a place. Private companies quickly saw the opportunity to collate the huge amounts of data needed to obtain accurate hensachi bell curve distributions and began operating practice exams (mogi shiken) in schools across Japan. From the mid-1970s onwards, hensachi increasingly became seen as the source of many educational ‘evils’ in Japan and there were many attempts to ban its use. It was blamed for cramming, examination hell, and a focus on educational scores rather than learning. The system was also being used by teachers and schools to short cut the real examination system. The final section of the paper explores why, despite these concerns, repeated predictions of the demise of hensachi have proved to be premature.